2023
DOI: 10.1177/10870547231171727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylphenidate Treatment on Olfactory Function in Children and Adolescents With ADHD

Abstract: Objective: This study aimed to research whether there is an olfactory disorder in ADHD, and if so, what is the effect of methylphenidate on this condition. Method: This is a cross-sectional study aiming to evaluate olfactory threshold, identification, discrimination and threshold, discrimination, and identification (TDI) scores in 109 children and adolescents, 33 of whom have ADHD without medication, 29 with ADHD with medication and 47 control groups. Result: In the post hoc tests, the mean odor discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A number of studies have reported olfactory deficits in individuals with ADHD. Children with ADHD have shown deficits in odor identification (Ghanizadeh et al, 2012;Karsz et al, 2008;Mercan Isik et al, 2023;Murphy et al, 2001), odor detection threshold (Ghanizadeh, 2010;Ghanizadeh et al, 2012) these findings contradict a separate study in which children and adolescents with ADHD showed greater olfactory sensitivity (Lorenzen et al, 2016;Romanos et al, 2008). Interestingly, methylphenidate, a standard medication for ADHD, has been shown to normalize these olfactory changes (Mercan Isik et al, 2023;Romanos et al, 2008).…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 87%
“…A number of studies have reported olfactory deficits in individuals with ADHD. Children with ADHD have shown deficits in odor identification (Ghanizadeh et al, 2012;Karsz et al, 2008;Mercan Isik et al, 2023;Murphy et al, 2001), odor detection threshold (Ghanizadeh, 2010;Ghanizadeh et al, 2012) these findings contradict a separate study in which children and adolescents with ADHD showed greater olfactory sensitivity (Lorenzen et al, 2016;Romanos et al, 2008). Interestingly, methylphenidate, a standard medication for ADHD, has been shown to normalize these olfactory changes (Mercan Isik et al, 2023;Romanos et al, 2008).…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 87%